Ainsley Iggo. 2 August 1924—25 March 2012. (14th December 2019) - Cervero, Fernando
Abstract : Ainsley Iggo's research was focused on the functional properties of sensory receptors in the skin and viscera. He developed a new electrophysiological technique for recording the electrical activity of individual afferent fibres and was the first to record such activity from single unmyelinated afferents, the smallest diameter afferents in sensory nerves. His seminal work contributed to the discovery of nociceptors; the sensory receptors that respond to injury and are at the origin of pain sensation. He also recorded the functional activity of many types of sensory receptor in the skin, muscle and viscera and classified their responses according to their adequate stimuli. These findings gave support to the specificity theory of sensation, particularly of pain. He described the morphology of individually identified receptors, thus providing direct evidence for the long-held assumption that distinct morphological types of skin receptors mediate distinct sensations. Later in life he contributed to studies of sensory neurons in the spinal cord and of the sensory electro-receptors found in animals such as the echidna and the platypus. A native of New Zealand, he moved to the UK in 1950 and spent most of his professional life at the University of Edinburgh, where he created a highly productive research group at the Veterinary School.